Conventions and nomenclature for double diffusion encoding NMR and MRI. Issue 1 (29th September 2015) - Shemesh, Noam; Jespersen, Sune N.; Alexander, Daniel C.; Cohen, Yoram; Drobnjak, Ivana; Dyrby, Tim B.; Finsterbusch, Jurgen; Koch, Martin A.; Kuder, Tristan; Laun, Fredrik; Lawrenz, Marco; Lundell, Henrik; et al.
Abstract : Stejskal and Tanner's ingenious pulsed field gradient design from 1965 has made diffusion NMR and MRI the mainstay of most studies seeking to resolve microstructural information in porous systems in general and biological systems in particular. Methods extending beyond Stejskal and Tanner's design, such as double diffusion encoding (DDE) NMR and MRI, may provide novel quantifiable metrics that are less easily inferred from conventional diffusion acquisitions. Despite the growing interest on the topic, the terminology for the pulse sequences, their parameters, and the metrics that can be derived from them remains inconsistent and disparate among groups active in DDE. Here, we present a consensus of those groups on terminology for DDE sequences and associated concepts. Furthermore, the regimes in which DDE metrics appear to provide microstructural information that cannot be achieved using more conventional counterparts (in a model‐free fashion) are elucidated. We highlight in particular DDE's potential for determining microscopic diffusion anisotropy and microscopic fractional anisotropy, which offer metrics of microscopic features independent of orientation dispersion and thus provide information complementary to the standard, macroscopic, fractional anisotropy conventionally obtained by diffusion MR. Finally, we discuss future vistas and perspectives for DDE. Magn Reson Med 75:82–87, 2016. © 2015 Wiley Periodicals, Inc.